Knowledge Authority and Value Degradation in the AI Era Rethinking Islamic Education - Madlubur Rhisky; Hasan Baharun (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2026)
The rapid advancement of Artificial Intelligence (AI) has not only transformed information access but has also shifted traditional knowledge authority toward algorithm-driven systems. Within Islamic education, this phenomenon triggers an epistemological dilemma and raises concerns regarding the degradation of moral values and academic character among learners. This study aims to analyze how AI transforms knowledge authority in Islamic education, identify the manifestations of value degradation it causes, and propose a reconstruction of the Islamic educational paradigm to integrate AI ethically and responsibly. This study employed a qualitative literature review approach, utilizing the interactive thematic analysis model of Miles, Huberman, and Saldaña. Peer-reviewed journal articles from Scopus, Web of Science, ERIC, and Google Scholar databases published between 2020 and 2026 were critically analyzed and synthesized from a philosophical-epistemological perspective. The findings indicate that AI has shifted teacher authority from an information ownership paradigm (information authority) toward an interpretive and ethical guidance paradigm (interpretive and ethical authority). Furthermore, excessive dependence on AI potentially triggers the degradation of essential educational values such as intellectual struggle (mujāhadah), the ethics of seeking knowledge (adab al-'ilm), truthfulness (ṣidq), and responsibility (amānah). To address this, this study proposes a reconstruction of the Islamic educational paradigm through a value-based AI integration framework, where teachers are repositioned as epistemic mentors and AI is utilized strictly as a supportive instrument. Theoretically, this study extends the discourse on educational technology by offering a theological-philosophical synthesis that preserves the authenticity of scholarly lineage (sanad) and morality in the digital era.